Optimalisasi Penjualan dan Stok Opname Melalui Penerapan Sistem Informasi Akuntansi Pada UMKM - NI LUH DE ERIK TRISNAWATI; NI KADEK AYU TRISNADEWI; NI MADE SRI AYUNI; KETUT SUMERDANA (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
The problem that is often experienced by UMKM that operate in the trading business is sales instability which is influenced by stock taking that is not well organized. This constraint encourages the need for an accounting information system in business management. The aim of this service is to implement an accounting information system as an effort to increase sales and manage stock of goods. The activity begins with initial observations to carry out situation analysis, followed by carrying out community service through designing the implementation of an accounting information system. Business actors are also given training to use point of sale applications in carrying out sales transactions which were previously carried out manually. With this training activity, business actors feel very helped, making it easier to achieve increased company performance and become the company's strength in facing competition.